Issues of training art teachers in the context of educational innovations - Galyna Padalka; Liudmyla Pankiv; Wang Xia; Wu Qirui; Zhang Shengwen; Hu Tingting (Revista on line de Política e Gestão Educacional)
The purpose of the work is to determine the personal qualities of a music teacher that contribute to the effectiveness of his artistic and educational activities in modern conditions, the theoretical development of the essence, content, and component structure of the categories “artistic empathy”, “style culture of performing musical works”, “artistic and performing self-efficacy of the individual”. Using the methods of questioning, testing, pedagogical observation, and analysis of lessons in the system of arts faculties of pedagogical universities of Ukraine and statistical processing of the materials obtained, the state of modern practice of professional training of future musicians is characterized. As a result of the study, it is argued that these qualities are among the dominant professional and personal qualities of a modern music teacher. The article confirms the prospects for forming these professional and personal qualities precisely in the process of special musical training of students.